Perencanaan lanskap wisata kesehatan di pesisir Desa Kusamba, Kecamatan Dawan, Kabupaten Klungkung - Raheni, Komang Indah Tri; Yusiana, Lury Sevita; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019, 2019)
Health tourism landscape planning in coastal Kusamba, Kusamba Village, Dawan sub-district, Klungkung Regency. Kusamba village is a village in eastern Klungkung that has coastal potential as a tourist destination. Kusamba coastal is famous for its marine products and traditional salt making, unfortunately that traditional salt making now lost it’s existence. Kusamba coastal also has the potential of nature that can be utilized as a health tourism using sea salt and black sand. The purpose of this study was to plan the existing landscape of the Kusamba coastal and to preserved natural products and traditional salt making. Method used in this study was field survey with observation technique, interview, distributing questionnaire, and literature study. The planning method applied was implemented Simonds planning process (2006) with some modification. The results showed that tourism activities and health tourism applied in coastal areas of Kusamba were salt spa and black sand therapy where is the visitors can relaxed their body with sea salt and black sands. It can be recommended that further research on development of nature tourism Kusamba need to held in order to explore Kusamba have coastal forest which is very potential as nature tourism.